HYPOTHYROIDISM IN INFANTS OF MOTHERS WITH GRAVES’ DISEASE: A CASE SERIES - Lordudass, Alexis Anand Dass; Wong, Jeanne Sze Lyn; Selveindran, Nalini M; Teoh, Sze Teik; Amin, Noor Arliena Mat; Tee, Pian Pian; Cheng, Hooi Peng; Gan, Cheng Guang; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Maternal hyperthyroidism may cause a wide spectrum of infantile thyroid abnormalities. The maternal thyroid status, presence of antithyroid antibodies and dose of antithyroid drugs(ATD) can affect thyroid alterations of the fetus and neonate. While hyperthyroidism in neonates of maternal Graves’ disease (GD) are well-described, hypothyroidism is less commonly reported. RESULTS We describe five infants with hypothyroidism born to mothers with GD. In our case series, three mothers were diagnosed with Grave’s Disease prior to pregnancy, one during pregnancy and one postnatally. Two mothers had elevated TSH-receptor antibodies (TRAb), the remainder did not have any levels checked. Four were treated with Carbimazole ranging 10-30 mg once daily (OD) and one was treated with Propylthiouracil 50 mg OD. All mothers had poorly controlled hyperthyroidism. Three infants developed central hypothyroidism from Day 9 to 2 months of life. They had low free-thyroxine (FT4) ranging between <3.2 to 7.5 pmol/L with inappropriately low-normal Thyroid Stimulating Hormone(TSH) levels of 0.018 to 3.385 mU/L. One infant had an initial hyperthyroid phase that was treated with Carbimazole prior to converting to hypothyroidism. Two infants developed primary hypothyroidism at Day 4 to 18 of life. Their TSH readings were high between 96.55 to 105 .29 mU/L with fT4 between 6.3 and 18.2 pmol/L. All five patients were started on L —Thyroxine. CONCLUSION Maternal gestational hyperthyroidism causes a hyperthyroid fetal environment due to increased thyroxine transfer which leads to suppression of the fetal hypothalamic-pituitary-thyroid axis and central hypothyroidism of the newborn. Primary hypothyroidism could be a result of transplacental passage of antithyroid drugs(ATD) during pregnancy or transplacental passage of 0maternal blocking antibodies. Early diagnosis and adequate treatment of mothers with GD is imperative to prevent the deleterious consequences of thyroid impairment during the neonatal period. Infants of maternal GD should be monitored for both hyperthyroidism and hypothyroidism.